4×4.5-3x=6.33
来源:学生作业帮助网 编辑:六六作业网 时间:2024/11/17 16:18:00
4×4.5-3x=6.334×4.5-3x=6.334×4.5-3x=6.33X=(18-6.33)/3=3.894×4.5-3x=6.3318-3x=6.336-x=2.11x=6-2.11x=3.
4×4.5-3x=6.33
4×4.5-3x=6.33
4×4.5-3x=6.33
X=(18-6.33)/3 =3.89
4×4.5-3x=6.33
18-3x=6.33
6-x=2.11
x=6-2.11
x=3.89
3=4×4.5-6.33=18-6.33=11.67
x=3.89
18-3x=6.33
18-6.33=3x
3x=11.67
x=3.89
x等于4,59
4×4.5-3x=6.33
一个“整式的乘法”的问题请先阅读下列解题过程,再仿做下面的问题.已知X*X + X - 1=0,求X*X*X + 2*X*X + 3的值.解X*X*X + 2X*X +3=X*X*X +X*X -X +X*X +X +3=X{X*X +X -1} +X*X +X -1 +4=0+0+4=4+ x + X*X + X*X*X=0.+ X*X + X*X*X
x+2x+3x+4x+5x+6x+7x+8x+9x=9x-8x-7x-6x-5x-4x-3x-2x-x.x等于多少?
(11)4x*4.5-3x=6.33(12)13x-7.5x=18.7*3(13)(x+4)/5=6(14)3.96+1.8x=20.16(15)12*6+8x=120
(11)4x*4.5-3x=6.33(12)13x-7.5x=18.7*3(13)(x+4)/5=6(14)3.96+1.8x=20.16(15)12*6+8x=120
(x-3/x-2)-(x-2/x-1)=(x-5/x4) -(x-4/x-3)
x-2x+3x-4x+5x.+99x-100x=25求解
2x+3x+4x+5x+x+6x+7x=100
x(x+1)+(x+2)+(x+3)+(x+4)+(x+5) = 27求x
X+X+X+(X-1)+(X-2)+(X-3)+(X-4)=10(X-3)+(X-4)
x+2/x+1-x+4/x+3=x+6/x+5-x+8/x+7 x=?
x^4+x^3+x^2+x+1=0,x^2006+x^2005+x^2004+x^2003+x^2002
x^2-3x=x-4
4,8-x=3x(x
4x-2(x-3)=x
x(x-4)=-3 x^2
化简 [3x/(x+2)-x/(x=2)]÷x/(x^2-4)化简 [3x/(x+2)-x/(x-2)]÷x/(x^2-4
写过程x(x-1)+2x(x+1)-3x(2x-5)-x(3x-2)+2x(2-x)=-5x(x-2)-4